Metal-doped zinc oxide nanostructures for nanogenerator applications: A review. (2023) - Kamal Ariffin, N.I.; Mamat, M.H.; Kamaruzaman, D.; Abdullah, M.H.; Parimon, N.; Yaakob, M.K.; Malek, M.F.; Vasimalai, N.; Suriani, A.B.; Mohamed, A.; Ahmad, M.K.; Rusop, M.
Abstract: Nanogenerators have been widely discussed and investigated in the literature due to their excellent development in various sectors and applications. There are two typical electricity generating mechanisms involved in nanogenerators, that include piezoelectric and triboelectric processes. The selection of materials in developing nanogenerator applications is vital in guaranteeing that the produced devices have decent output performance. Zinc oxide (ZnO) is a semiconductor material with a large bandgap that significantly influences numerous technological sectors, including nanogenerator fabrications. Besides, numerous methods have been used to synthesize ZnO nanostructures for various applications. The improvement and alterations need to be performed based on the produced ZnO nanostructures for better device performance. Previous studies have reported the effect of metal-doped ZnO nanostructures on the properties and characteristics of the nanogenerator applications. Hence, the brief review of the different techniques used in the fabrication of ZnO nanostructures and the performance enhancement of the ZnO-based nanogenerator, which consists of the doping process and the development of nanogenerator applications, have been presented in this paper.